2007
DOI: 10.1038/sj.bjc.6603981
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydiae and Mycoplasma infections in pulmonary MALT lymphoma

Abstract: Chlamydia pneumoniae, Chlamydia trachomatis and Chlamydia psittaci were detected at low frequencies (o20%) among 69 pulmonary mucosa-associated lymphoid tissue (MALT) lymphomas, 30 other lymphoproliferative disorders (LPD) and 44 non-LPD. The incidence of individual Chlamydiae was generally higher in MALT lymphoma than non-LPD, although not reaching statistical significance. Mycoplasma pneumoniae DNA was not detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 16 publications
1
22
2
Order By: Relevance
“…The incidence of gastric MALT lymphoma is closely related to a helicobacter pylori infection; however, the current belief is that the incidence of pulmonary MALT lymphoma may be associated with an infection or smoking. 4) In this study, 10 patients had a history of pulmonary infection, long-term smoking, or both that supports the related report. Another study found that some autoimmune diseases such as Sjogren's syndrome and Hashimoto's thyroiditis can promote the incidence of pulmonary MALT lymphoma, but the specific mechanism remains unclear.…”
Section: Aetiologysupporting
confidence: 77%
“…The incidence of gastric MALT lymphoma is closely related to a helicobacter pylori infection; however, the current belief is that the incidence of pulmonary MALT lymphoma may be associated with an infection or smoking. 4) In this study, 10 patients had a history of pulmonary infection, long-term smoking, or both that supports the related report. Another study found that some autoimmune diseases such as Sjogren's syndrome and Hashimoto's thyroiditis can promote the incidence of pulmonary MALT lymphoma, but the specific mechanism remains unclear.…”
Section: Aetiologysupporting
confidence: 77%
“…70,99,103 No conclusion can be drawn from the available information on antibiotic treatment in these lymphomas; the published data are scanty and possibly biased by the preferential publication of positive results.…”
Section: Other Bacterial Infections At Different Malt Sitesmentioning
confidence: 98%
“…65 Further studies are warranted to investigate the potential pathogenetic role of the microorganism because no data demonstrating a causal relationship has yet been provided 102 and other microorganisms (Chlamydophila) were reported as possibly involved with MALT lymphoma of the lung. 103 Moreover, a previous history of lymphocytic interstitial pneumonia, which is frequently associated with autoimmune disorders, or of other rare nonneoplastic pulmonary lymphoid proliferations (follicular bronchiolitis and nodular lymphoid hyperplasia) support the concept that lymphoma may also evolve from these noninfectious inflammatory processes. 104 …”
Section: Achromobacter Xylosoxidans and Pulmonary Malt Lymphomamentioning
confidence: 98%
“…However, the rate of Chlamydia infection was judged to be below 20%, and no evidence for mycoplasms was found, suggesting that these pathogens are rarely associated with pulmonary MALT lymphoma. 37 In contrast to this, another study assessed a total of 5 patients with pulmonary MALT lymphoma who all tested positive for CP, whereas no evidence for C pneumoniae or trachomatis was detected. 38 Achromobacter xylodosaxidans is another potential candidate pathogen recently demonstrated in patients with pulmonary MALT lymphoma.…”
Section: Pulmonary Malt Lymphomamentioning
confidence: 99%